1987
DOI: 10.2307/1939849
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Defense Against Different Marine Herbivores: Are Amphipods Insect Equivalents?

Abstract: The Structurally similar diterpenoid alcohols pachydictyol-A and dictyol-E are produced by the brown seaweed Dictyota dichotoma. This seaweed and several related species that also produce these compounds are known to be relatively low preference foods for tropical fishes and urchins. We evaluated the effect of various concentrations of these compounds on feeding by the three common types of herbivores that co-occur with Dictyota in coastal North Carolina. Fish (Diplodus holbrooki), sea urchins (Arbacia punctul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
322
4
17

Year Published

1992
1992
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 338 publications
(358 citation statements)
references
References 80 publications
15
322
4
17
Order By: Relevance
“…All these substrate situations undoubtedly elicit different chemicals that the amphipods could be responding to. Hay et al (1987) have shown that gammarid amphipods will make dramatically different food choices in response to structurally very similar algal metabolic compounds.…”
Section: Resultsmentioning
confidence: 99%
“…All these substrate situations undoubtedly elicit different chemicals that the amphipods could be responding to. Hay et al (1987) have shown that gammarid amphipods will make dramatically different food choices in response to structurally very similar algal metabolic compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, Cladophora spp. were avoided by parrotfish and some surgeonfish (Paul and Hay, 1986), yet were consumed by Z. flavescens (Wylie and Paul, 1988) and the amphipod Amphithoe longimana (Hay et al, 1987a). Ulva spp.…”
Section: Discussionmentioning
confidence: 99%
“…Ulva spp. were avoided by the sea urchins Strongylocentrotus droebachiensis (Van Alstyne and Houser, 2003), P. lividus , and L. variegatus (Lowe, 1974), the spottail pinfish Diplodus holbrooki (Hay et al, 1987a), and A. longimana (Duffy and Hay, 1994). However, Ulva spp.…”
Section: Discussionmentioning
confidence: 99%
“…We regard cyanobacterial and microalgal secondary metabolites in the light of their defensive action, these substances stand in marked contrast to known biotoxins striking vertebrate animals during "water blooms" and "red tides" (Gol'din, 2009). The defensive activity has a disastrous influence on vital functions of competitors and/or plant-feeders, and causes stress, repellent and deterrent effects, but not obligatory death (Cembella, 2003;Amsler, 2008;Berry et al, 2008 responses are very close to inhibitory activity of terrestrial plants-producers of allelochemics for the defense from the other plants or herbivorous arthropods and microbial pathogens (Gol'din, 1995;2009;Gol'din and Gol'dina, 2002;Hay et al, 1987;Paul et al, 2007;Berge et al, 2010).…”
Section: Introductionmentioning
confidence: 99%